Elicitazioni plurilingui nella classe d’italiano LS a Malta - Caruana , Sandro; Fenech, Krystle (Incontri. Rivista europea di studi italiani, 2022)
Plurilingual elicitations in Italian for foreigners’ classrooms in MaltaThrough elicitation teachers involve learners in the process of discovering language and they use various means in order to do so: these include verbal cues (paraphrasing, questioning etc.) and non-verbal ones (pictures, gestures etc.). In this paper I refer to data collected in the Italian language classroom in Malta, in a small-scale study based on twelve lessons, carried out by three different trilingual (Maltese/English/Italian) teachers. Learners are 13-14 year-old Maltese nationals. In my analysis I present information related to the way teachers use elicitation in order to encourage their learners to produce vocabulary and simple sentences in Italian. Examples are provided to illustrate exchanges in which using learners’ language prior competences is a pedagogically-valid strategy. Data reveal that teachers resort to various elicitation techniques, and that they rely heavily on their plurilingualism. This indicates that teaching a foreign language in a bilingual context lends itself to situations wherein elicitation occurs by resorting to learners’ L1 and to their knowledge of other languages.